KAJIAN HUKUM KEDUDUKAN BANGUNAN DI ATAS HAK PAKAI ATAS TANAH YANG TELAH DI BATALKAN (Di Tinjau Dari Peraturan Pemerintah Nomor 40 Tahun 1996 Tentang Hak Guna Usaha, Hak Guna Bangunan Dan Hak Pakai Atas Tanah) - Mahmud Jaelani; Abdul Mukmin (Yuriska: Jurnal Ilmiah Hukum, 2018)
The right to use is regulated in Article 41 through Article 43 which is further regulated in Government Regulation No. 40 of 1996 concerning Right to Cultivate, Right to Build and Right to Use of Land Article 41 to Article 58. In Article 41 paragraph (1) of Law Basic Agrarian Law, is defined as the Right to Use is the right to use and / or collect proceeds from land that is directly controlled by the state or land of the Property of another person, who gives authority and obligations specified in the decision to grant it by an official authorized to give it or in an agreement with the owner of the land, which is not a lease agreement or land processing agreement, everything originating does not conflict with the spirit and provisions of this law.So that the cause of the cancellation of the second right is the position of the building above the usufructuary rights to the land that has been cancelled. The position of the building this case is not only in the physical sense concerning the location and magnitude of the building alone, more than that it has a legal meaning concerning the legal position of the building. This is related to ownership rights and land rights attached to it. The method used in this study is a normative research study with legislation as primary legal material, books, literature as secondary legal material and information and data as secondary material from this study.In principle, the matter that causes the Right to Use of Land can be canceled is the expiration of the term or canceled by the authorized official, the management right holder or the landowner before the expiry date, released voluntarily by the right holder before the term expires, the right of use is revoked, abandoned, the land is destroyed and the Right of Use holder does not qualify as the Right to Use holder. Whereas in relation to the position of the building above the Use of Land Rights by the Indonesian Citizen who has been cancelled depends on the agreement that accompanies when the right to use is granted, but for foreigners through the right to use can transfer their assets through inheritance.